1994
DOI: 10.1177/154079699401900201
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Acceptability of Instructional Practices for Students with Severe Disabilities in General Education Settings

Abstract: This study investigated 51 instructional methods specifically targeted as best practices for the education of students with severe disabilities. A survey was mailed to 120 project directors, professors, administrators, and researchers who provided direct and/or indirect services to individuals with severe disabilities. A total of 53 surveys (44%) was returned and 51 were included in the final data analysis. Participants judged each method on familiarity, soundness, and appropriateness for implementation in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…Effective strategies for enhancing relationships included collaboration, cooperative learning, direct instruction of social interaction skills, and peer tutoring. Billingsley and Kelley (1994) asked project directors, professors, administrators, and researchers whether 51 instructional methods used with students with significant disabilities were acceptable for use in general education. The methods were grouped into setting events, delivery systems, naturalistic strategies, antecedent conditions, transfer of stimulus control, consequent events, and generalization/maintenance.…”
Section: Descriptors: School Inclusion Best Practices Moderate To Smentioning
confidence: 99%
“…Effective strategies for enhancing relationships included collaboration, cooperative learning, direct instruction of social interaction skills, and peer tutoring. Billingsley and Kelley (1994) asked project directors, professors, administrators, and researchers whether 51 instructional methods used with students with significant disabilities were acceptable for use in general education. The methods were grouped into setting events, delivery systems, naturalistic strategies, antecedent conditions, transfer of stimulus control, consequent events, and generalization/maintenance.…”
Section: Descriptors: School Inclusion Best Practices Moderate To Smentioning
confidence: 99%
“…In particular, the research literature includes few investigations of the effects of specific instructional manipulations on the performance of students with intellectual disabilities in the general curriculum. Although there is evidence that the behavior analytic procedures commonly used by special educators (e.g., shaping, response prompting) have utility in inclusive settings (Agran, Alper, & Wehmeyer, 2002;Billingsley & Kelley, 2004;Ryndak & Alper, 2003), instructional approaches specific to accessing the general curriculum have received scant attention, particularly for students with mental retardation. As Wehmeyer, Lance, and Bashinski (2002) indicated, although the 1997 Amendments emphasized the adoption of school-wide interventions to promote access to the general curriculum (e.g., instruction in problem solving), their utility for students with intellectual disabilities is neither a concern or an issue that has been systematically investigated.…”
mentioning
confidence: 99%
“…Still 4 1 % of the research involved nondisabled peers in some capacity. Naturalistic teaching approaches and realistic school settings, while challenging to the researcher, reflect methods and conditions that are more often judged to be socially valid and compatible with the current trend toward teaching students with disabilities in inclusive school programs (Billingsley & Kelley, 1994). The primary benefits of using integrated school settings for research include (a) increased relevance of procedures to practitioners, (b) the potential for directly involving peers (as mediators, tutors, confederates, etc.)…”
Section: Effective Instructional Approachesmentioning
confidence: 99%
“…Despite the documented prevalence of response prompts recently and in the 1980s (Demchak, 1990), the work of Repp and Karsh and that of Gast, Wolery, Doyle, and colleagues calls into question the continued use of some extended prompting hierarchies, such as a traditional SLP (verbal, verbal + model, verbal + physical), which may be inefficient for many learners (in terms of trials to criterion and error rates), may be difficult to use, and may promote prompt dependency in learners, less task engagement, and more disruptive behaviour during instruction. Others have found that practitioners question the social validity of some prompt approaches and error-correction methods which involve extensive physical assistance from an adult (Billingsley & Kelley, 1994;Wolfe, 1994). As recommended by Demchak (1990), response prompts should be designed to suit an individual student's skills (e.g., imitative learners would receive modelling) and preferences (e.g., some learners find physical guidance aversive), rather than to adopt standardised approaches.…”
Section: Effective Instructional Approachesmentioning
confidence: 99%
See 1 more Smart Citation